The body & the bike: A kinetic chain analysis of cycling overuse injury - Visentini, P. (Journal of Science and Cycling, 2015)
Introduction: Physiotherapists, osteopaths, doctors, bike-fitters and other cycling injury managers, are perfectly placed to help the ever-growing cycling community to become better riders as well as to prevent pain and injury. Whilst there are a myriad of "bike set-up" protocols available, some more evidence based than others, very few "bike set-up" practitioners take into account the body and its complex neuromuscular and kinematic abilities. There is no argument that understanding the geometry around optimal configuration is an important component for efficiency and injury prevention (Wisbey-Roth 2009), and some leading "Bike-Fit" proponents argue the neuromuscular perspective (Steve Hogg 2007). There are also endless references to optimal pedalling technique- "spinning the pedals", "elegant", "wipe the mud of the shoe", "like a duck swimming" or "smooth and continuous"(Colson from Brukner and Khan 2012), implying that optimising activation patterns has a distinct role in good pedaling technique.